Direct Anterior Approach in THA without a fracture table in cases with associated adduction contractures of hip - an evaluation - Rajat Saran; Rakesh Mishra (International Journal of Medical Research and Review, 2014)
Introduction: The prerequisites of an optimal approach for total hip arthroplasty include a relatively short skin incision, easy accessibility to the acetabulum and proximal part of the femur, minimal damage to muscle bundles with minimal blood loss & neuronal injury. Direct anterior approach of hip arthroplasty fulfils most of the criteria’s. The aim of this prospective study is to evaluate the functional outcome of the patient, assess the utility and convenience of the direct anterior approach to the hip in a supine position on a standard radiolucent operation table, obviating the need of a fracture table and its complications, in cases of hip joint pathologies necessitating a total hip arthroplasty especially those associated with other conditions like adductor contractures, where both the deformities demand to be dealt with at the same sitting.Methods: This study comprises of total hip arthroplasties performed on sixteen hips in eleven patients between October 2011 to May 2014 at tertiary care teaching hospital. Indications in nine patients were idiopathic avascular necrosis, one had a non union of fracture femoral neck and one fracture trochanter with secondary osteoarthritis.Results: All the patients had an uneventful recovery. There was a significant improvement in the symptoms of all the patients. They were pain free. The limb length discrepancy was corrected in all except one patient who had a lengthening of the operated leg by two millimetres.Conclusion: It proves to be convenient with rewarding results in a rapid functional outcome. It does have a significant learning curve